Review of global and Russian trends in the hydrogen energy development - E. A. Vechkinzova; L. P. Steblyakova; E. V. Sumarokova (Управление)
In the article, based on a comparative analysis and analytical generalization of publications, program and regulatory documents from different countries, the authors consider the prospects for the development of the hydrogen market. Most publications are currently focused on the technical and technological aspects of hydrogen energy, solving the problem of increasing the efficiency of methods for the production, transportation, distribution and storage of hydrogen fuel. In all countries of the world, the technology for the production of highly environmentally friendly “green” hydrogen is at an early stage, which makes it highly dependent on government initiatives to develop hydrogen projects and government funding of both scientific research in this area and ongoing projects. Peaks of interest in the field of hydrogen energy are associated with changes in the fossil energy markets, which makes the development of this technology unsustainable. Many countries are ready to invest in the development of hydrogen energy, and, given the growth in demand for hydrogen, are ready to export it at an affordable price. The results of the study indicate that the trends in the development of hydrogen energy in Russia are fundamentally aligned with global trends. At the same time, the high resource and scientific and technological potential allows Russia to fully focus its strategy on its implementation, not only developing the domestic market, but also acting as an exporter of hydrogen and expanding international cooperation in this area.